2020
DOI: 10.1186/s12958-020-00676-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between anti-Müllerian hormone and vitamin 25(OH)D serum levels and polycystic ovarian syndrome in adolescent females

Abstract: Background High anti-Müllerian hormone (AMH) levels and 25-hydroxyvitamin D [25(OH)D] deficiency have been associated with polycystic ovarian syndrome (PCOS) in adult women, and implicated in its pathogenesis. Herein we determined if the level of both AMH and 25(OH)D are altered in adolescent females with clinical features of PCOS. Methods This is a cross-sectional study utilizing a retrospective chart review of 128 patients aged 12–20 referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Women with PCOS and hirsutism have been found to have lower 25(OH)D levels than BMI-matched controls [169,172], which may be explained by an association of vitamin D with androgens or SHBG [170,173]. In a cross-sectional study in adolescents, participants with PCOS had higher levels of AMH and lower levels of 25(OH)D than in the group without PCOS [174]. They concluded that since traditional clinical markers of PCOS may be physiological in adolescents, AMH and 25(OH)D can be used as surrogate markers of PCOS risk in this population.…”
Section: Vitamin D Status and Polycystic Ovary Syndromementioning
confidence: 99%
“…Women with PCOS and hirsutism have been found to have lower 25(OH)D levels than BMI-matched controls [169,172], which may be explained by an association of vitamin D with androgens or SHBG [170,173]. In a cross-sectional study in adolescents, participants with PCOS had higher levels of AMH and lower levels of 25(OH)D than in the group without PCOS [174]. They concluded that since traditional clinical markers of PCOS may be physiological in adolescents, AMH and 25(OH)D can be used as surrogate markers of PCOS risk in this population.…”
Section: Vitamin D Status and Polycystic Ovary Syndromementioning
confidence: 99%
“…Its active form, 1,25-dihydroxy vitamin D 3 is localized in many organs, such as kidney, liver, brain and ovary ( Xu et al, 2016 ). In the female reproductive system, vitamin D can regulate anti-Müllerian hormone (AMH) secretion in the granulosa cells and consequently affect FSH level ( Simpson et al, 2020 ). However, its role in POI pathogenesis is controversial as some claimed it did not influence pathophysiological process of POI, while others reported vitamin D deficiency was correlated with coagulation and was a primary factor for POI due to follicular dysgenesis and aromatase level decrease ( Kebapcilar et al, 2013 ; Ersoy et al, 2016 ).…”
Section: Vitaminsmentioning
confidence: 99%
“…Recently, vitamin D has been implicated in reproductive health and pregnancy outcomes [ 12 , 13 ]. Clinical studies have shown that vitamin D supplementation can lower androgen levels, lower anti-Mullerian hormone (AMH) levels [ 14 , 15 ], normalize the metabolic profile, and regularize periods in women with polycystic ovarian syndrome (PCOS) [ 16 , 17 ]. In fact, low serum 25(OH)D concentrations have been linked to problems of infertility [ 18 , 19 ], endometriosis [ 20 ], polycystic ovary syndrome (PCOS) [ 16 , 17 , 21 , 22 ], as well as adverse pregnancy outcomes, including spontaneous abortions [ 23 ], gestational diabetes [ 24 , 25 ], bacterial vaginosis [ 26 ], preeclampsia [ 27 , 28 ], neonatal hypocalcemia [ 29 ], prematurity, and low birth weight [ 30 ], as well as fetal and infant growth disorders [ 31 ].…”
Section: Introductionmentioning
confidence: 99%